A REVIEW ON MINDFULNESS AND NURSING STRESS AMONG NURSES - Said, Zaini; Kheng, Goh Lei (Universitas Medan Area, 2018)
Previous research has been done on mindfulness and nursing stress but no review has been done to highlight the most up-to-date findings, to justify the recommendation of mindfulness training for the nursing field. The present paper aims to review the relevant studies, derive conclusions, and discuss future direction of research in this field. A total of 19 research papers were reviewed. The majority was intervention studies on the effects of mindfulness-training programs on nursing stress. Higher mindfulness is correlated with lower nursing stress. Mindfulness-based training programs were found to have significant positive effects on nursing stress and psychological well-being. The studies were found to have non-standardized intervention methods, inadequate research designs, small sample size, and lack of systematic follow-up on the sustainability of treatment effects, limiting the generalizability of the results. There is also a lack of research investigation into the underlying mechanism of action of mindfulness on nursing stress. Future research that addresses these limitations is indicated.